Genetic investigation confirmed the clinical phenotype of congenital chloride diarrhea in a Hungarian patient: a case report - Éva Dávid; Dóra Török; Katalin Farkas; Nikoletta Nagy; Emese Horváth; Zsuzsanna Kiss; György Oroszlán; Márta Balogh; Márta Széll (BMC, 2019)
Abstract Background Congenital chloride diarrhea (CCD, OMIM 214700) is a rare autosomal recessively inherited condition characterized by watery diarrhea, hypochloremia and metabolic alkalosis. Mutations of the solute carrier family 26, member 3 (SLC26A3, OMIM 126650) gene are responsible for the disease. The gene encodes a transmembrane protein, which is essential for intestinal chloride absorption. Case presentation Here we report a Hungarian boy, presenting the clinical phenotype of CCD. The patient born at 32 weeks of gestation and underwent surgery for abdominal distension and intestinal obstruction related to malrotation. After recovery, electrolyte replacement therapy was necessary due to several periods of diarrhea. After exclusion of other possible causes, increased chloride concentration in the feces supported the diagnosis of CCD. The diagnosis was confirmed by molecular genetic testing. Direct sequencing revealed compound-heterozygosity for a frameshift mutation c.1295delT (p.Leu432Argfs*11) and the known Polish founder mutation c.2024_2026dupTCA (p.Ile675_Arg676insLeu). Conclusions Here we present the clinical symptoms of the first patient in Hungary diagnosed with CCD. Based on the clinical symptoms, stool analysis and genetic testing, the diagnosis of CCD was established. Our study provides expansion for the mutation spectrum of the SLC26A3 gene and the genetic background of CCD.